Qohelet and ‘Heretic’ Harpers’ Songs - Fischer, Stefan 1966- (2002)
The book of Qohelet has a seven-fold refrain. In it Qohelet calls for joy. These texts are dependent upon the Egyptian ‘heretic’ Harpers’ Songs of the New Kingdom. The ‘heretic’ Harpers’ Songs agree not only in the content and reason for joy, but also in the use of idioms, phrases and themes, which occur not just in the key texts but also elsewhere in Qohelet. The ‘heretic’ Harpers’ Songs were transmitted to Israel together with the Egyptian love songs, probably already in premonarchic times.